UJI BEBERAPA KONSENTRASI EKSTRAK RIMPANG JERINGAU (Acorus calamus L.) UNTUK MENGENDALIKAN HAMA WALANG SANGIT (Leptocorisa acuta Thunberg) PADA TANAMAN PADI GOGO (Oryza sativa L.) - Desita Salbiah; Nizwan Harefa (UIR Press, 2018)
ABSTRACT Government efforts in supporting the increase in national rice production, namely optimizing dry land by planting upland rice. Rice seed bug (Leptocorisa acuta Thunberg) is a potential pest that at certain times become an important pest on the upland rice plants, therefore needed to control is using organic insecticide such as sweet flag rhizome extract. This research was aimed to obtain an effective concentration sweet flag rhizome extract (Acorus calamus L.) to control rice seed bug pest (Leptocorisa acuta Thunberg) on the ​​upland rice plant (Oryza sativa L.). The research was conducted at the Experimental Garden and Plant Pest Laboratory, Faculty of Agriculture, Riau University, Pekanbaru from January to May 2018. The experimentally by using a completely randomized design (CRD), which consist of five concentration sweet flag rhizome extract treatments are 0 g.l-1 water, 20 g.l-1 water, 40 g.l-1 water, 60 g.l-1 water and 80 g.l-1 water. The treatments repeated four times, therefore, twenty experimental units. The results showed that the concentration of 80 g.l-1 water was an effective concentration to control rice seed bug with the fastest start time of death at 1,25 hours, the fastest LT50 at 30,25 hours and the total mortality rate of 87,50%. Keywords: Organic insecticide, Sweet Flag Rhizome, Rice Seed Bug, Upland Rice